2008
DOI: 10.1142/s1793524508000072
|View full text |Cite
|
Sign up to set email alerts
|

An Impulsive Predator-Prey System With Beddington–deangelis Functional Response and Time Delay

Abstract: This paper deals with an impulsive predator-prey model with Beddington–DeAngelis functional response and time delay, in which the evolution of the predators takes them through two stages, juvenile and mature. It is assumed that only mature predators are able to hunt for prey and reproduce and the time delay is understood as being the time spent by the juvenile predators from birth to maturity. It is first seen that the dynamics of the model can be completely determined through the use of a reduced system consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Similarly to Zhang et al [18], it can be shown that I (t) is globally asymptotically stable by using stroboscopic map. As a consequence, system (4.1) always has a pest-free periodic solution ( I (t), 0).…”
Section: Impulsive Release Of the Entomopathogenic Nematodesmentioning
confidence: 70%
“…Similarly to Zhang et al [18], it can be shown that I (t) is globally asymptotically stable by using stroboscopic map. As a consequence, system (4.1) always has a pest-free periodic solution ( I (t), 0).…”
Section: Impulsive Release Of the Entomopathogenic Nematodesmentioning
confidence: 70%
“…Especially, based on the economic theory proposed by [17], an algebraic equation is established to investigate the effect of harvest effort on some population in the ecosystem. Compared with the models proposed in the references [46,32,57,13], the advantages of the models proposed in [59,60,61,33] are that these models not only investigate the interaction mechanism of the prey-predator with stage structure for predator but also offer a simpler way to study the effect of harvest effort on the ecosystem from an economic perspective. As mentioned above, [60,61,59] have investigated some biological-economic systems by using the differential-algebraic model.…”
Section: Model Formulationmentioning
confidence: 99%
“…Furthermore, the functional response also has an important impact on the behavior of biological dynamical systems [25][26][27][28][29]. We note the fact that, in biology, very high nutrient concentration may inhibit the growth of microorganisms actually, and the microorganisms will die eventually as the nutrient concentration increasing unlimitedly.…”
Section: Introductionmentioning
confidence: 96%